Development of adaptive rice variety to non-tidal swamp: Growth evaluation of backcrossed progenies (BC1F1) and its parents, Inpago 5 and Inpara 8 - Nabilah Amiros; Rujito Agus Suwignyo; Mery Hasmeda; Fikri Adriansyah; Entis Sutisna Halimi; Erizal Sodikin (Universitas Padjadjaran, 2022)
AbstractRice (Oryza sativa L.) cultivation in non-tidal swamp is severely constrained by abiotic stresses, i.e., submerged stress in the vegetative phase and drought stress in the generative phase. The development of rice varieties that have dual-tolerant to those abiotic stresses can improve adaptability and increase productivity. Efforts to obtain adaptive varieties under those abiotic stress conditions are being carried out by selecting the parents and crossing them, and has resulted in the population of BC1F1. The research was carried out on April – June 2021 at greenhouse of the Agriculture Faculty, Sriwijaya University. The study aimed to evaluate the growth of BC1F1 progenies and parental varieties, Inpago 5 (live well in drought condition) and Inpara 8 (inherited Sub1 gene). The results showed that the vegetative growth (plant height and number of total tillers) of BC1F1 was influenced by genetics of the parents. While generative growth parameters, Inpago 5, as a recipient parent, had the highest number of total spikelets per panicle (181.42 grains), the lowest percentage of sterile spikelets (25.05%) and the lowest biomass dry weight (27.88 g). Inpara 8, as a donor parent, had the highest average number of productive tillers (8.34 tillers), took the longest time to flower (76 days), and the shortest time to harvest (115 days). Then, BC1F1 got the highest average number of total spikelets per plant (1348.2 grains), weight of 1000 grains (25.49 g), and grains dry weight (9.71 g). Based on study, the most growth traits of BC1F1 were genetically influenced by the parents, indicated a segregation from the parents. The plants will be used for second backcrossing (BC2F1) and a molecular selection using Marker-Assisted Backcrossing (MABC) method to obtain plants that have Sub1 gene and the closest characteristic to recipient parent (Inpago 5).Keywords: dual tolerance, Inpago 5, Inpara 8, Oryza sativa AbstrakBudidaya padi (Oryza sativa L.) di lahan rawa lebak sangat terkendala dengan cekaman abiotik cekaman terendam pada fase vegetatif dan cekaman kekeringan pada fase generatif. Pengembangan varietas padi yang memiliki dual tolerant terhadap cekaman abiotik tersebut dapat memperbaiki daya adaptasi dan meningkatkan produktivitasnya. Upaya untuk mendapatkan variietas adaptif dengan kondisi cekaman abiotik tersebut sedang dilakukan dengan melakukan seleksi tetua dan menyilangkannya, dan telah menghasilkan aksesi BC1F1. Penelitian dilaksanakan pada bulan April – Juni 2021 di greenhouse Fakultas Pertanian, Universitas Sriwijaya. Tulisan menyampaikan hasil evaluasi pertumbuhan progeni BC1F1 dan kedua varietas induk, Inpago 5 dan Inpara 8. Hasil penelitian menunjukkan pertumbuhan vegetatif (tinggi tanaman dan jumlah anakan total) BC1F1 dipengaruhi oleh genetik dari kedua induk. Sementara parameter pertumbuhan generatif, Inpago 5 (induk resipien) memiliki jumlah gabah total per malai tertinggi sebanyak 181,42 butir; persentase gabah hampa terendah sebesar 25,05%; bobot kering biomassa terendah sebesar 27,88 g. Inpara 8 (induk donor) memiliki rata-rata jumlah anakan produktif terbanyak (8,34 anakan), waktu berbunga terlama (76 hari), dan waktu panen tercepat (115 hari). Kemudian BC1F1 memiliki jumlah gabah total per rumpun tertinggi sebanyak 1348 butir), bobot 1000 butir gabah tertinggi (25,49 g), dan berat kering gabah (9,71 g). Berdasarkan hasil penelitian, sebagian besat karakteristik pertumbuhan populasi BC1F1 dipengaruhi secara genetik oleh kedua induk yang mengindikasi adanya segregasi sifat dari keduanya. Tanaman akan digunakan pada silang balik generasi kedua (BC2F1) dan diseleksi secara molekular menggunakan metode Marker-Assisted Backcrossing (MABC) untuk mendapatkan tanaman terbaik yang memiliki gen Sub1 dan karakter agronomi paling dekat dengan Inpago 5.Kata Kunci: dual toleransi, Inpago 5, Inpara 8, Oryza sativa